Geneologi Pemikiran Hazairin mengenai Pembaharuan Hukum Islam - Ahmadi, Ahmadi; Hilmanul Hakim, M. Fikry (Indonesian Proceedings and Annual Conference of Islamic Law And Sharia Economic (IPACILSE), 2023)
Kitab turats has been a guideline for Muslims in carrying out sharia according to Islamic law since ancient times. The work of scholars and ulama' mutaqoddimin is very popular among Muslims, especially in Indonesia until now. However, in the 20th century, a figure emerged who reformed Islamic law from the work of previous scholars. This figure is named Hazairin. There are several reasons or factors underlying Hazairin's reform of Islamic law in the Turats. Some of the factors include changes and differences in the condition of the community environment in several regions, especially in Indonesia. This study is really interesting to discuss, because it will review the reasons for a Hazairin to reform Islamic law or called geneoligi, where the law has previously been a guide for Muslims in faith from century to century.